2020
DOI: 10.1177/1078155220978446
|View full text |Cite
|
Sign up to set email alerts
|

Accurate determination of glomerular filtration rate in adults for carboplatin dosing: Moving beyond Cockcroft and Gault

Abstract: Objective Carboplatin is a cytotoxic chemotherapy drug developed in the 1980s which is still widely used today across various tumour types. Despite its common application, there remains a significant controversy and practice variation on its unique method of dosing by area under the curve (AUC). One potential reason for this variability stems from the reliance of using an estimated glomerular filtration rate (eGFR) as an extrapolation of the measured GFR (mGFR) which the commonly used Calvert equation was orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Recently, White-Koning et al [16] reported in a pharmacokinetic study that CKD-EPI is one of the more accurate formulas to predict carboplatin clearance in the Calvert formula. This finding has been confirmed in a recent statement article by Tsang et al [17]. For further studies, a complementary approach could be the therapeutic drug monitoring that allows prediction of unbound carboplatin clearance from carboplatin total plasma concentration [18].…”
Section: Discussionmentioning
confidence: 53%
“…Recently, White-Koning et al [16] reported in a pharmacokinetic study that CKD-EPI is one of the more accurate formulas to predict carboplatin clearance in the Calvert formula. This finding has been confirmed in a recent statement article by Tsang et al [17]. For further studies, a complementary approach could be the therapeutic drug monitoring that allows prediction of unbound carboplatin clearance from carboplatin total plasma concentration [18].…”
Section: Discussionmentioning
confidence: 53%
“…In clinical practice, carboplatin dose is usually determined through the Calvert equation, most commonly using eGFR equations. 38 Two French models (Thomas, and Chatelut, n = 403 patients) demonstrated that incorporating both Scys and Scr accurately predicts CaCl. 37,39 In another cohort of 491 patients with solid tumors, the Calvert equation based on CKD-EPIcr-cys was the best equation to predict CaCl, the least biased, with the lowest mean absolute percentage error (MPAE) and the lowest P20 (percentage of patients with MPAE over 20%) when compared to all other models used to predict GFR based on Scr alone (CKD-EPI, CG, MDRD (Modification of Diet in Renal Disease Study equations), incorporated into the Calvert or Thomas/Chatelut models.…”
Section: Cystatin C As a Filtration Marker In Patients With Solid Tumorsmentioning
confidence: 98%
“…In clinical practice, carboplatin dose is usually determined through the Calvert equation, incorporating eGFR. 40 Two French models (Thomas and Chatelut, n5403 patients) demonstrated that incorporating both serum creatinine and cystatin C accurately predicts CaCl. 39,41 In another cohort, the Calvert equation on the basis of CKD-EPICr-Cys was the best equation to predict CaCl and the least biased, with the lowest mean absolute percentage error and the lowest percentage of patients with mean absolute percentage error over 20% versus equations used to predict GFR on the basis of creatinine alone.…”
Section: Boxmentioning
confidence: 99%